2011
DOI: 10.1073/pnas.1105450108
|View full text |Cite
|
Sign up to set email alerts
|

Signature of hydrophobic hydration in a single polymer

Abstract: Hydrophobicity underpins self-assembly in many natural and synthetic molecular and nanoscale systems. A signature of hydrophobicity is its temperature dependence. The first experimental evaluation of the temperature and size dependence of hydration free energy in a single hydrophobic polymer is reported, which tests key assumptions in models of hydrophobic interactions in protein folding. Herein, the hydration free energy required to extend three hydrophobic polymers with differently sized aromatic side chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
160
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(177 citation statements)
references
References 39 publications
(59 reference statements)
16
160
1
Order By: Relevance
“…They used atomic force microscopy to pull out collapsed hydrophobic polymers in aqueous solution and to measure the force required. Their results [47] show interesting correlations with hydrophobic free energy values measured by solubility studies.…”
Section: Related Topicssupporting
confidence: 51%
See 1 more Smart Citation
“…They used atomic force microscopy to pull out collapsed hydrophobic polymers in aqueous solution and to measure the force required. Their results [47] show interesting correlations with hydrophobic free energy values measured by solubility studies.…”
Section: Related Topicssupporting
confidence: 51%
“…Recently Li and Walker [47] have shown that mechanical pulling provides such a method. They used atomic force microscopy to pull out collapsed hydrophobic polymers in aqueous solution and to measure the force required.…”
Section: Related Topicsmentioning
confidence: 99%
“…By studying polymers of different monomer types, Li and Walker analyzed how hydrophobic free energy contributes to the pulling energetics. The results showed strong correlations with the Kauzmann-Tanford approach to hydrophobic free energy but also showed quantitative differences (31). The pulling free energy values were smaller than expected from solvent transfer studies; the pulling experiments may well contain contributions from pairwise hydrophobic interactions as well as from hydrophobic hydration.…”
Section: Resultsmentioning
confidence: 66%
“…The results reported here reinforce the need to find other approaches to measuring hydrophobic free energy and enthalpy in protein folding. A promising alternative approach has been reported recently: the hydrophobic factor in polymer collapse has been studied with collapsed hydrophobic polymers in aqueous solution by pulling out the polymer using atomic force microscopy and analyzing the force required (31). By studying polymers of different monomer types, Li and Walker analyzed how hydrophobic free energy contributes to the pulling energetics.…”
Section: Resultsmentioning
confidence: 99%
“…3A. The properties of the more hydrophobic chains, and observation of hydrophobic clusters for some unfolded proteins by NMR (71,72), suggest that a description similar to a classic hydrophobic collapse mechanism may be appropriate in these cases (30,31,73). A second effect that needs to be taken into account is that the amplitudes of chain collapse with temperature will be affected by the sign of the interactions within the polypeptide.…”
Section: Resultsmentioning
confidence: 99%